UJI AKTIVITAS ANTIBAKTERI AIR REBUSAN CAMPURAN BATANG SERAI, DAUN SIRIH DAN RIMPANG JAHE TERHADAP PERTUMBUHAN Escherichia coli - Ginting, Aditya Karsa Imanuel; Indriarini, Desi; Setianingrum, Elisabeth; Amat, Anita Shinta (Universitas Nusa Cendana, 2023)
Background: Diseases that caused by E. coli bacteria such as urinary tract infections, prostatitis, pelvic inflammation, infections of the lining of the brain in newborns and diarrhea or digestive tract infections. Treatment of this disease still uses antibiotics which over time will become resistant, with the expensive medical costs and the side effects that can be obtained later so it can be sought with alternative herbal plants such as lemongrass stem, betel leaf and ginger rhizome, which are some of them have antibacterial activity. Objectives: To test the antibacterial activity of mixture boiled water of lemongrass stem (Cymbopogan citratus), betel leaf (Piper betle) and ginger rhizome (Zingiber officinale) against the growth of Escherichia coli bacteria. Method: The type of research used is a true experimental design with research design used is a posttest only control group test. Testing the antibacterial activity of mixture boiled water of lemongrass stem, betel leaf and ginger rhizome using the liquid dilution method. The research sample consisted of ciprofloxacin as positive control, aquades as negative control, and concentration groups of 100%, 50%, 25%, 12.5%, `6.25%, 3.12%, 1.56% with three repetitions for each group. Result: Based on the results of bacterial testing with dilution method using the mixture boiled water of lemongrass stem, betel leaf and ginger rhizome, the minimum resist rate test results were obtained at concentration 100% and there was no minimum killing rate. Conclusion: The mixture boiled water of lemongrass stem, betel leaf and ginger rhizome did not have antibacterial activity against the growth of Escherichia coli.